Experimental research on magnesium phosphate cements modified by red mud. (20th January 2020) - Liu, Yuantao; Qin, Zhaohui; Chen, Bing
Highlights: Novel magnesium phosphate cements were prepared with the solid waste-red mud. The addition of red mud in MPC can improve the properties significantly. The pore structure of MPC can be optimized by red mud. The microstructures were observed and the new hydration products were analyzed. Abstract: The main concern of this article is to understand the influences of red mud on the properties of magnesium phosphate cement (MPC), which were determined in terms of the fluidity, setting characteristic, temperature evolution during the hardening stage, mechanical properties, water resistance, hydration products, pore structure and microstructure. The results showed that the fluidity can increase to a value of 272.5 mm at a level of 20% red mud, and red mud was found to decrease the exothermic reaction intensity of the fresh mortar and to prolong the setting time to 25 min during the hardening stage. The mortar prepared with suitable addition of red mud presented with improved mechanical properties and enhanced water resistance during the whole ageing period, and the group containing 20% red mud yielded the highest compressive strength of 90.2 MPa at 28 days. Then, the pore structure was measured by low-field nuclear magnetic resonance (LF-NMR), which was found that adding red mud can reduce the total porosity and form more small pores. Moreover, the microstructure and the hydration products of the samples were tested by X-ray diffraction (XRD), scanning electron microscopy (SEM) along with energy dispersive spectrometer (EDS). The obtained results illustrated that red mud can fill in the microcracks, making the structure denser, and also formed with some new hydrates. The present work aimed at the utilization of red mud and the results illustrated that MPC can be modified by red mud significantly.